1998
DOI: 10.1177/000331979804900706
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Lumen Femoral Vein Catheterization as Vascular Access for Hemodialysis

Abstract: Prospectively from January 1991 to January 1993, the efficacy and complications of 104 polyurethane, double-lumen femoral vein catheterizations (FVC) in 96 renal failure patients were studied. Ambulation was allowed in the hospital as well as at home while the catheter was in. There were 53 males and 43 females, with ages ranging from 13 to 87 (mean, 48.3 +/- 19.7) years. Forty-eight patients had chronic renal failure and 48 had acute renal failure. The catheters were used for 1 to 26 days (mean, 8 +/- 5 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
1
8
1
Order By: Relevance
“…Natalie et al [12], in a similar study reported incidence rate of immediate complications of 10%, arterial puncture 5%, haematoma 1.25% and failure of canulation in 3.75%. Also other studies reported arterial puncture in 4.2 -9% [12,13] which is higher than our study. The lower rate in our study could be attributed to the skill and experience of the operator, extra precaution and limiting unsuccessful attempts to a maximum of three.…”
Section: Discussioncontrasting
confidence: 78%
“…Natalie et al [12], in a similar study reported incidence rate of immediate complications of 10%, arterial puncture 5%, haematoma 1.25% and failure of canulation in 3.75%. Also other studies reported arterial puncture in 4.2 -9% [12,13] which is higher than our study. The lower rate in our study could be attributed to the skill and experience of the operator, extra precaution and limiting unsuccessful attempts to a maximum of three.…”
Section: Discussioncontrasting
confidence: 78%
“…Infection was the major complication reported with double-lumen femoral vein catheters consistent with our study. 18 The complications of DLC were consistent with the previous reports. The number of complications reported with DLC were higher as compared to those with AVF.…”
Section: Discussionsupporting
confidence: 90%
“…Use of the subclavian vein should be avoided because of the adverse effects it can have on AVF or AVG creation in the upper limbs later on. Indwelling of up to 3 weeks is permissible, but because fever and infection have been found to be unrelated to the length of indwelling, a longer period is possible if there are no signs of fever or infection (19). Naturally, during this period of catheter use, efforts should be made to establish a permanent VA through new construction or reconstruction.…”
Section: Chaptermentioning
confidence: 99%